2003
DOI: 10.1139/w03-009
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phenanthrene and naphthalene by aBurkholderiaspecies strain

Abstract: Burkholderia sp. TNFYE-5 was isolated from soil for the ability to grow on phenanthrene as sole carbon and energy source. Unlike most other phenanthrene-degrading bacteria, TNFYE-5 was unable to grow on naphthalene. Growth substrate range experiments coupled with the ring-cleavage enzyme assay data suggest that TNFYE-5 initially metabolizes phenanthrene to 1-hydroxy-2-naphthoate with subsequent degradation through the phthalate and protocatechuate and beta-ketoadipate pathway. A metabolite in the degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…In addition, Burkholderia spp. TNFYE-5 and BS3702 and Burkholderia cepacia VUN 10001 were capable of degrading phenanthrene, and fluorene, phenanthrene, and pyrene (100 mg/l), respectively, as a sole carbon source 2,6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Burkholderia spp. TNFYE-5 and BS3702 and Burkholderia cepacia VUN 10001 were capable of degrading phenanthrene, and fluorene, phenanthrene, and pyrene (100 mg/l), respectively, as a sole carbon source 2,6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Tech.,7 (4),[639][640][641][642][643][644][645][646][647][648][649][650][651][652] No. of cfu/mL bacteria and the metabolites formed during the degr adation was r epor ted by oth er wor ker s (Pinyakong et al, 2000;Moody et al, 2001;Kang et al, 2003;Kim et al, 2005). Wang et al (2008) reported phenanthrene degradation by microbial consortium under saline condition with phthalic acid as metabolite.…”
Section: Description Of Va3 Strain (Stenotrophomonas Maltophilia)mentioning
confidence: 99%
“…For enzymes assays and metabolites determination thermophilic isolate was grown in mineral salt medium (MSM) [9] 4. Batch cultures were incubated in the dark at 60°C.…”
Section: Microorganism Isolation and Cultivationmentioning
confidence: 99%
“…Pathways by which mesophilic bacteria degrade aromatic hydrocarbons under aerobic conditions as well as enzymes involved in the metabolism of these hydrocarbons are well-studied [1][2][3][4]. On the other hand, little is known on the growth of thermophilic microorganisms on aromatic hydrocarbons, such as benzoic acid, cresols and phenols [5][6][7].…”
Section: Introductionmentioning
confidence: 99%